A duck in a sock : with four phonics stories - Rae, Elspeth, 1973-; Rae, Rowena (Rae, Elspeth, 1973- Meg and Greg, 2020)
"Meg and Greg are hanging out for the summer doing what ten-year-olds do--helping an injured duckling, finding a lost pet fish, saving ranch animals from a wildfire and catching a wandering sloth! Jump inside to join Meg and Greg on their adventures" -- Page 4 of cover.